Optimization of the motor-sensory system of young volleyball players based on the functional state assessment of regulatory systems - Gorelik, V.; Vlasov, V.; Makarova, V. (Journal of Physical Education and Sport, 2018)
Purpose of the study is to improve the motor-sensory system of young athletes based on the assessment of the functional state of regulatory systems. Materials and methods. The study was carried out on the basis of a Specialized Children's and Youth Sports School of the Olympic Reserve (SCYSSOR) 2 "Krasnyye kryl'ya" (Togliatti, Russia). The study involved 50 students who were divided into two groups of 25 people each, namely the main group (MG) and the comparison group (CG). To assess the functional state of the children`s organism and determine parameters of the vegetative balance, neurohumoral regulation, the heart rate variability (HRV) analysis was used with the hardware-software complex "Varicard 2.51." The study of psychophysiological indicators was carried out with the help of the computer program "Researcher of Temporal and Spatial Properties of Human - Version 2.1." The following tests were used in it: determining the reaction time to a moving object (RMO) and determining the reaction time to a choice. These techniques are used as a physiological test to determine the level of the relationship between the processes of excitation and inhibition in the cerebral cortex, both in a state of relative rest and under the influence of physical exertion. The response time to a choice is one of the variants of a complex sensorimotor reaction, since it is necessary to differentiate the signal (one signal needs to be reacted, and the other one does not have to respond). To assess the technical and physical preparedness of the practitioners, a number of control tests (standards) were used. Results. As a result of optimization of the functional state of the regulatory systems in the schoolchildren of 8-9 years, the parameters of motor abilities and technical preparedness of the subjects are improving, as well as the psychophysiological indices of schoolchildren. Conclusion. The received data clearly demonstrates that at optimization of a functional condition of an organism of children there is more effective training to technical methods of game of volleyball and development of impellent abilities of engaged pupils of 8-9 years.